Strategic Planning Model for Excellent Elementary Schools Based on the Wetland Ecosystem in North Banjarmasin - Suhaimi; Ni'mah; Noorahim W (Postgraduate, University of Mataram, 2026)
This study aims to develop a strategic planning model for excellent elementary schools based on the wetland ecosystem in the North Banjarmasin District. A qualitative approach with a case study design was employed at two high-performing public elementary schools. Data were collected through in-depth interviews, participant observation, and document analysis, and subsequently analyzed using an interactive model. The findings indicate that the characteristics of the wetland ecosystem—such as seasonal flooding, peatland, and infrastructure limitations—significantly impact the effectiveness of school strategic planning. Implementation still faces obstacles regarding curricula and facilities that are not yet fully adaptive to the environment. However, high community participation serves as a primary supporting factor in school development. This research produced a strategic planning model consisting of five key components: wetland-based strategic environmental analysis, environment-adaptive vision and mission formulation, contextual curriculum development, adaptive facilities management, and the strengthening of school-community partnerships. This model demonstrates that integrating ecological aspects into strategic planning can enhance the relevance, effectiveness, and sustainability of school management. Theoretically, this study enriches the field of educational management through an ecosystem-based approach, while practically, it provides a reference for schools and policymakers in designing contextual and adaptive strategic plans in wetland regions.